Protecting Students-Consumers Interests in Universities and Colleges - Nguyen Trong Diep; Dinh Tran Ngoc Huy; Pham Thi Hong Nhung; Ly Thi Hue; Nguyen Dinh Trung (Celebes Scholar pg, 2022)
This study will investigate ways in which universities and colleges can better protect the interests of their student customers by creating a new learning environment and improving the quality of the services provided to students in lecture halls. The ultimate goal of this research is to increase student satisfaction as customers. The authors of this research derive certain educational lessons for students in Vietnam and other developing markets based on their observations, experiences, synthesis analyses, and dialectical approaches. According to the findings of this survey, students are the universities' primary customers. The level of happiness a company's customers feel may be directly attributed to the quality of the service provided. Customers will first have a positive impression of a company if the service provider gives them with high-quality items that are able to fulfill their requirements.